y_n=log x_n, n =2,3,4,...and y_n-(n-1)/n y_(n-1)=1/n log n, with y_2=log sqrt2, how do you prove that x_n=(n!)^(1/n)?

1 Answer
Jan 24, 2017

By induction

Explanation:

Note that as y_n = log(x_n), we have x_n = e^(y_n) (assuming the natural logarithm. Using a different base will not change the structure of the proof, however). Additionally, note that y_n = 1/nlog(n)+(n-1)/ny_(n-1) by the second given relation.

Proof: (By induction)

Base Case: For n=2, we are given y_2 = log(sqrt(2)), meaning

x_2 = e^log(sqrt(2)) = sqrt(2) = (2!)^(1/2)

Inductive Hypothesis: Suppose that x_k = (k!)^(1/k) for some integer k>=2.

Induction Step: We wish to show that x_(k+1) = [(k+1)!]^(1/(k+1)). Indeed, examining y_(k+1), we have

y_(k+1) = 1/(k+1)log(k+1)+k/(k+1)y_k

=1/(k+1)[log(k+1)+klog(x_k)]

=1/(k+1)[log(k+1)+klog((k!)^(1/k))]

=1/(k+1)[log(k+1)+log(k!)]

=1/(k+1)log(k!(k+1))

=1/(k+1)log((k+1)!)

=log([(k+1)!]^(1/(k+1)))

meaning x_(k+1) = e^(y_(k+1)) = [(k+1)!]^(1/(k+1)), as desired.

We have supposed true for k and shown true for k+1, thus, by induction, x_n = (n!)^(1/n) for all integers n>=2.